MTHFR C677T gene polymorphism and the severity of coronary lesions in acute coronary syndrome. Issue 49 (December 2017) - Li, Miao-Nan; Wang, Hong-Ju; Zhang, Ning-Ru; Xuan, Ling; Shi, Xiao-Jun; Zhou, Tong; Chen, Bin; Zhang, Jun; Li, Hui
Abstract : Abstract: The association between methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism, circulating levels of homocysteine (Hcy), and the severity of coronary lesion in patients with acute coronary syndrome (ACS) remains unknown. Consecutive ACS patients were included. MTHFR C677T polymorphisms were determined via amplification refractory mutation system-polymerase chain reaction (ARMS-PCR). Gensini scores were used to evaluate the severity of coronary lesions. Three hundred ten ACS patients were included, and grouped according to the MTHFR C677T polymorphism variant: CC (n = 78, 25.2%), CT (n = 137, 44.2%), and TT (n = 95, 30.6%) groups. No significant differences were detected with respect to baseline characteristics. Patients in TT group had significantly higher Hcy, and significantly lower folic acid (FA) levels as compared with those in the other 2 groups ( P < .05 for both). More importantly, patients with TT had more severe coronary lesions as compared with those from the other 2 groups, as evidenced by higher Gensini scores ( P < .05 for both); however, no significant differences were observed with respect to the numbers of affected coronary arteries, or the number, length, and diameter of stents implanted in each group ( P > .05 for all). On multivariate logistic regression analysis, presence of a T allele in MTHFR C677T was found to be independently associated with higher circulating Hcy (odds ratio [OR] = 1.06, 95% confidence interval [CI]: 1.01–1.12, P = .024), and higher Gensini scores (OR: 1.01, 95% CI: 1.00–1.02, P = .046). MTHFR C677T TT polymorphism was associated with higher Hcy levels and more severe coronary lesions in patients with ACS.